Design of Electrical Power Telemetering System Using Microcontroller Device Via GSM - Mohanad Abdulhamid (TEKNO, 2024)
Traditionally, the reading of energy meters is done by human operators who move from house to house collecting readings. This exercise requires huge labor operator numbers and a lot of time to achieve a complete reading of meters in a particular area. This paper endeavors to reduce this problem by using a telemetering system. With this system, power can be measured from a remote site. To achieve this, readings from an energy meter on site are processed by a microcontroller device that sends the energy consumption information to a Global System Mobile (GSM) module. The GSM module then sends this information using microwaves to a particular mobile subscriber who receives it in the form of a Short Message Service (SMS). The reading is also transmitted to a web-based telemetering system through a server. In the remote site, a remote computer which can access the internet can obtain data from the server through the internet. The microcontroller is developed in such a way that it achieves communication between the energy meter and the server using the Transmission Control Protocol (TCP) protocol. Software programs are also developed to facilitate the transfer of data to the user at remote sites. With the web-based telemetering system connected to the internet, electrical energy measurements can be accessed globally. The efficiency of the transmission channel is important for the success of both SMS and web-based telemetering systems.